SIMBOL AGAMA HINDU SEBAGAI PRODUK TATO DI KUTA - Ni Putu Suwartini; I Made Sendra; Yohanes Kristianto (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Tourists are interested in creative industry products with Balinese style and culture. The symbol of religion is a business opportunity developed by Bali's creative industries. Commodification of the sacred symbol of Hinduism in the form of tattoos occurs because of the tourist demand for tattoos in the form of Hindu religious symbols. This research was conducted in Kuta. Determination of informants using basic informant techniques and key informants. Data was collected through interviews conducted with Jero Bendesa Adat Kuta as the base informant and tattoo artist as the key informant. The data analysis technique used is descriptive qualitative. The results of this study indicate that the commodity of Hindu holy symbols in the form of tattoos as creative industrial products in Kuta occurs because of the demand for tourists and because there are no rules regarding the use of Hindu symbols in the form of tattoos. Commodification occurs in the value of the sacred symbols of Hindu religion which are sacred to commercial value. Commodification occurs in the function of the sacred symbol of Hinduism which functions as a sacred object into an object that functions as an art. This commodification does not change the original form of the sacred symbol of Hinduism, only a few variations are added such as flowers, lines, circles and so on.